Pregnancy with Twins with Preeclampsia - Ismatova Malikа Muxiddinovna; Azimova Zilola Sobirovna (Central Asian Journal of Literature, Philosophy and Culture, 2022)
Preeclampsia has a significant long-term effect on the health of both mothers and babies. Preeclampsia-related pregnancy complications increase the morbidity and mortality of pregnant women and their fetuses by 5–8%. The recent advancement of assisted reproductive technology, combined with a rise in the number of elderly pregnant women, has resulted in pregnancy incidence with twins. Twins pregnant women have a 2–3 times greater risk of developing preeclampsia than singleton pregnant women and it happens sooner and progresses faster. It is more severe and may appear in an atypical way.